Analisa Perpindahan Panas Pada Alat Pengering Pisang Tipe Rak Kombinasi Tenaga Surya dan Biomassa - Sakka, Ambo; Mangalla, Lukas Kano; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2018)
So far, most farmers have drained agricultural products by drying directly under the hot sun. The drying process by drying directly requires intensive labor, longer time and requires a large amount of land. The purpose of this study is to find out the heat transfer analysis that occurs in rack type dryers that utilize moving air flow into the device naturally and then the air is heated by utilizing the heat of solar radiation collected at solar collectors and also utilizing biomass energy used to accelerate drying process of the product in the drying chamber. The data obtained were taken by using Thermocouple CC type (Cooper Constanta), Solar Powermeter, Anemometer, Thermo-Hygrometer and Scales. The results of the study that the heat transfer analysis on the rack type dryer with the drying process using solar collectors as heat absorbers and biomass energy then combined. The results obtained for solar power efficiency is 55.852%, biomass energy efficiency of 58.127%, and combination efficiency of 69.935 %.Keywords: Dryer type rack, solar collector, biomass, drying variation, temperature, efficiency.